Docking study, Synthesis, Characterization and Preliminary cytotoxic evaluation of new 1,2,3,4-tetrahydroppyrimidine derivatives - Mohammed, Noor M. (Journal of Contemporary Medical Sciences, 2022)
Objective: This study resolved that1 these anew synthesized analogs1 may 1be embodied as1 an 1exploitable foundation of new 1anticancer1 1agents to competition breast 1cancer Methods: By means of The crystal1 structure of Histone deacetylases (HDACs-8) with Vorinostat (SAHA) as 1a co-crystalized1 ligand 1was gained1 from 1the protein 1data-bank 1 (PDB 1code 4QA0) as a result 1of 1docking the compounds (V a,s, V b,s, V a,t and V b,t) give 1good docking 1scores compared1 to the standard. 1 Compounds (V a,s, V b,s, V a,t and V b,t) was synthesized1 by multistep procedures1 from the reaction of intermediate derivatives (IV a,b) and the thiosemicarbazide or semicarbazide . The chemical1 structures1 of the1 target compounds11 and 1their intermediates1 were1 confirmed by 1FT-IR and1H 1NMR Results: The in-vitro cytotoxicity1 assay (MTT assay) demonstrated1 that compounds1 V a,t and V b,t showed1 good inhibition 1ratios in Breast1 cancer cell line1 (MCF-7) and human colon adenocarcinoma (HRT-18) 1comparable with drug1 control Vorinostat (SAHA). Conclusion: 1From the docking1 study, it was1 concluded1 that C=S moiety were very1 1successful to bind 1tightly to the zinc binding group of HDAC enzyme by making numerous 1interaction modes.